2011
DOI: 10.1038/ki.2010.351
|View full text |Cite
|
Sign up to set email alerts
|

Urine neutrophil gelatinase-associated lipocalin is a marker of graft recovery after kidney transplantation

Abstract: Delayed graft function (DGF), especially long-lasting DGF, complicates kidney transplant outcome. Neutrophil gelatinase-associated lipocalin (NGAL) is an acute kidney injury marker; therefore, we tested whether urine NGAL could predict DGF, prolonged DGF (lasting over 14 days), or the quality of kidney function in transplant recipients without DGF (non-DGF). We collected urine samples from 176 recipients transplanted with deceased donor kidneys before and various days after transplantation. A total of 70 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
88
2
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 36 publications
6
88
2
11
Order By: Relevance
“…There is a limited literature investigating the utility of NGAL for the diagnostic and prognostic evaluation of AKI in kidney transplantation. Hollmen and colleagues [7], also the authors of the paper commented on here, previously found that urine NGAL from the recipient on the first post-transplant day was of moderate utility to predict DGF, particularly prolonged DGF that correlated with worse 1-year graft survival. Similarly, others have shown that a variety of biomarkers of renal tubular injury/damage [8-12] or serum cystatin C (a marker of kidney function/glomerular filtration rate (GFR)) [11,13] can similarly diagnose AKI secondary to DGF in the early post-transplant period better than a combination of the usual clinical parameters of kidney function (serial monitoring of serum creatinine and urine output) with known DGF risk factors (ischemia times, and so on).…”
mentioning
confidence: 80%
“…There is a limited literature investigating the utility of NGAL for the diagnostic and prognostic evaluation of AKI in kidney transplantation. Hollmen and colleagues [7], also the authors of the paper commented on here, previously found that urine NGAL from the recipient on the first post-transplant day was of moderate utility to predict DGF, particularly prolonged DGF that correlated with worse 1-year graft survival. Similarly, others have shown that a variety of biomarkers of renal tubular injury/damage [8-12] or serum cystatin C (a marker of kidney function/glomerular filtration rate (GFR)) [11,13] can similarly diagnose AKI secondary to DGF in the early post-transplant period better than a combination of the usual clinical parameters of kidney function (serial monitoring of serum creatinine and urine output) with known DGF risk factors (ischemia times, and so on).…”
mentioning
confidence: 80%
“…Se le considera una lesión por isquemia y reperfusión (5) cuyos mecanismos fisiopatológicos involucran el estrés oxidativo, la disfunción mitocondrial y la activación inmunológica (7), lo que no permite la recuperación completa de las células renales, predispone a la atrofia y la muerte celular (8), aumenta el riesgo de rechazo agudo y crónico (3) y la estancia hospitalaria, y reduce la supervivencia del injerto renal (3,6,(9)(10)(11)(12).…”
unclassified
“…Aunque en la actualidad se sabe mucho sobre la fisiopatología de la función retardada del injerto, son pocas las estrategias de tratamiento conocidas (6); algunos tratamientos exitosos de la lesión por reperfusión en modelos animales no han sido efectivos en humanos (5,12), lo cual se explicaría por la detección tardía de la función retardada del injerto (8), ya que los biomarcadores actuales, que incluyen la creatinina sérica y la diuresis, son poco sensibles para predecirla (11,13). El hallazgo de nuevos biomarcadores que detecten en forma no invasiva y temprana la función retardada del injerto, permitiría la implementación de tratamientos para limitar el daño (3,6,14,15) y mejorar el resultado a largo plazo del injerto renal (8,16).…”
unclassified
See 2 more Smart Citations